Fluorescent in situ hybridization (FISH) as a diagnostic tool for Williams-Beuren syndrome - Souza, Deise Helena de [UNESP]; Moretti-Ferreira, Danilo [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP] (Sociedade Brasileira de Genética, 2007)
Fluorescent in situ hybridization (FISH) with commercial probes covering the elastin gene (ELN) was used to determine the frequency of the 7q11.23 deletion in 18 children clinically diagnosed with Williams-Beuren syndrome (WBS). A de novo deletion was detected in 15 of the children (83%). Diagnostic investigation for WBS started late in childhood (median = 5.8 years). All the children showed facial features typical of the syndrome, mental retardation and developmental delay. Over-friendliness was observed in the majority of cases. Clinodactyly of the 5th finger (n = 13), cardiovascular disease (n = 9), loquacity (n = 9), low birthweight (n = 8), and failure to thrive (n = 9) were observed only in those children with the deletion. Respiratory problems (n = 9), though not previously reported in the literature, was a common finding in the group studied. Our results confirmed that FISH is useful in identifying 7q11.23 deletions in cases of WBS. Clinical manifestations were more evident in the deletion-positive children.
Keywords: 7q11.23 deletion; ELN; FISH; Williams-Beuren syndrome